PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L) PADA BERBAGAI POLA JAJAR LEGOWO DAN JARAK TANAM - Donggulo, Candra V; Lapanjang, Iskandar M.; Made, Usman (AGROTEKBIS, 2018)
This study aims to get the right pattern Legowo row on each plant spacing; get Legowo row patterns are better on growth and yield of paddy; get better spacing on growth and yield of paddy. The study design randomized complete block design (CBD) with two factors, the first factor was spacing of the second stage and the second factor was the pattern Legowo row with 3 levels thus obtained 6 treatment combinations. Each combination treatment was repeated three times as a group so that the required 18 experimental plots. The results showed that the adoption of patterns Legowo row 2: 1 at a spacing of 20 cm x 20 cm resulted in higher plants while a spacing of 25 cm x 25 cm pattern Legowo row 3: 1 resulted in higher plants. Implementation patterns Legowo row 4: 1 to produce tillers and panicles number per clump more, whereas usage patterns Legowo row 3: 1 resulted in higher grain with an average of 7.29 tonnes ha-1 compared to other plant spacing pattern.